Suicide Risk Management in Psychiatric Hospitals : A Clinical and Medico-Legal Approach in Indonesian Mental Health Services - Bianda Adeti Patriajaya; Raden Wisnu Munazhat Akbar (International Medical Journal Corp. Ltd, 2026)
Suicide remains a major global public health concern, particularly among individuals with psychiatric disorders, and continues to present significant challenges in psychiatric hospital settings. In clinical practice, inadequate risk assessment, inconsistent monitoring, and unclear medico-legal responsibilities may compromise patient safety and increase potential liability. This study aims to analyze suicide risk management in psychiatric hospitals by integrating clinical experience with medico-legal perspectives to improve patient safety and healthcare accountability. A descriptive qualitative approach was used, based on clinical observations and a review of hospital protocols and relevant medico-legal frameworks in Indonesian mental health services. The findings suggest that effective suicide risk management requires not only comprehensive clinical assessment and continuous monitoring but also clear and consistent medico-legal guidance. Key challenges include variability in clinical practices, limited staff training, inadequate documentation, and ambiguity in legal accountability. Strengthening interdisciplinary collaboration, improving documentation practices, and aligning clinical protocols with legal standards are essential steps to enhance patient safety. In conclusion, an integrated clinical and medico-legal approach is crucial in managing suicide risk in psychiatric hospitals and in supporting safer and more accountable healthcare systems.